Evaluating the 2023–2024 record dry-hot conditions in the Amazon in the context of historical compound extremes - Vanessa Ferreira; Allan Buras; Jakob Zscheischler; Miguel Mahecha; Anja Rammig (Environmental Research Letters, 2025)
Since 2023, the Amazon rainforest has experienced unprecedented compound drought and heatwaves (CDHW). These events are closely linked to low soil moisture (SM) and high vapor pressure deficit (VPD), and have significant impacts on the Amazon ecosystem. In this study, we examine CDHW and concurrent low-SM/high-VPD events in the Amazon from 1981 to 2024, with a particular focus on the record-breaking drought of 2023–2024. Our findings reveal that CDHW events generally coincide with low-SM/high-VPD conditions, with most occurring during the well-documented droughts of 1983, 1997–1998, 2010, 2015–2016, and 2023–2024. The 2023–2024 period stands out with a record-high number of compound events and the most extensive coverage, with CDHW and low-SM/high-VPD conditions affecting 50% of the Amazon region during the austral springs of 2023 and 2024. The results also indicate that both CDHW and low-SM/high-VPD events have become more frequent, prolonged, and widespread in the Amazon since 2000. The Mann–Kendall tests also reveal an increasing trend of +0.5 events per year for CDHW and +0.6 for low-SM/high-VPD. Additionally, our findings highlight that the 2023–2024 period is not only marked by record-breaking CDHW events but also by unprecedented concurrent low-SM/high-VPD conditions.